High safety of agarose-based fillers. Personal observation - E.I. Karpova; A.A. Martynov; A.V. Vlasova; E.G. Privalova; Yu.Yu. Chebotareva; Iu.K. Akulinina; M.I. Glushkova; M.I. Stantsov; V.V. Grikh; E.I. Arhangelskaya (Russian Journal of Clinical Dermatology and Venereology, 2026)
Restoring lost volume with dermal fillers is a well-established aesthetic technique that utilizes various tissue-injectable materials, such as hyaluronic acid (HA), calcium hydroxyapatite, collagen, poly-L-lactic acid, agarose gel (AG). While HA-based implants remain the market leaders, there is a risk of adverse reactions if enzyme-induced degradation of these gels is necessary. Agarose-based gel is considered safe because it can be easily dissolved and removed from the injection site by administering normal saline and water for injection. Objective. To investigate the effect of solvents (normal saline and water for injection) on the rate of induced degradation of agarose gel in vitro and in vivo. Material and methods. A clinical observation of 5 patients was performed to evaluate the feasibility of controlled dissolution of an agarose-based filler using normal saline and water for injection. Agarose-based gels (at concentrations of 1.5 and 2.5%) were subjected to induced degradation by two solutions: 0.9% sodium chloride and water for injection. The induced degradation process was assessed by studying the physicochemical and rheological properties of the gel in vitro and ultrasound imaging of soft tissues in vivo. Results. Both agents effectively dissolve the AG-based gel. In vitro studies revealed the lowest stability in samples exposed to water for injection as the solvent, indicating significantly faster filler degradation compared to those treated with normal saline. In vivo, water for injection also showed greater dissolution capacity than normal saline. The AG-based filler bolus was completely degraded after a single use of water for injection, which was confirmed by ultrasound imaging. Conclusion. The efficacy and safety of using normal saline and water for injection to induce agarose gel degradation were demonstrated.